Prescription trends of gastric acid suppressants and association with potential adverse events in Korea: a real-world cross-sectional study - Min Jeong Je; Jeong Min Go; Shin Yeong Kim; Min-Gul Kim; Hankil Lee; Ha-Lim Jeon; Jae Hyun Kim (Therapeutic Advances in Gastroenterology, 2025)
Background: Recent changes in the acid-related disease market, particularly the emergence of potassium-competitive acid blockers (P-CABs), require an updated analysis of trends in gastric acid suppressant utilization. Objectives: As the use of P-CAB expands globally, a cross-sectional study is needed to assess its association with potential adverse events from a pharmacovigilance perspective. Design: Cross-sectional study. Methods: We analyzed gastric acid suppressant use at prescription and patient levels using the Health Insurance Review and Assessment National Patient Sample database (2014–2020). Prescription-level analysis included the annual prescriptions for histamine-2 receptor antagonists (H2RAs), proton pump inhibitors (PPIs), and P-CABs, and proportion of visits by acid-related indications. Patient-level analysis examined annual trends in drug use and clinical characteristics. Logistic regression was used to estimate prevalence odds ratios (ORs) for potential adverse events among drug users and non-users according to the drug class. Results: In 2020, H2RAs were primarily prescribed for gastritis and duodenitis (64.5%), whereas PPIs (55.4%) and P-CABs (58.6%) were primarily used to treat gastroesophageal reflux disease. H2RA prescriptions declined in 2019, whereas the use of P-CAB increased following the approval of tegoprazan in 2018. Patients aged 40–64 years and female users were predominant across all classes of gastric acid suppressants. P-CAB use was significantly associated with osteoporosis (OR = 1.17; 95% confidence interval (CI): 1.13–1.20), pneumonia (OR = 1.65, 95% CI: 1.55–1.75), and acute kidney injury (OR = 1.39, 95% CI: 1.20–1.61). Conclusion: P-CABs have reshaped the prescription landscape of gastric acid suppressants. Further longitudinal cohort studies are required to evaluate long-term safety in routine clinical practice.